The Influence of inflammatory factors (IL-6, CRP, NLPR, D-Dimer, LDH) on the PaO2/FiO2 ratio, in patients with severe and critical degrees of COVID-19 - Harnoto, Yulia Octaviany; Assagaf, Ali; Pratiwi, Dewi Indah Noviana; Isa, Mohamad; Nurrasyidah, Ira; Kusumawardhani, Erna (RSUP Dr. Kariadi, 2023)
BACKGROUND: Several types of inflammatory biomarkers that are important in severe and critical Covid-19 infections include: levels of IL-6, C-reactive protein (CRP), lactate dehydrogenase (LDH), D-Dimer and neutrophil-lymphocyte platelet ratio (NLRP), which are independent variables. Meanwhile, the severity of Covid-19 infection can be determined by measuring the PaO2 /FiO2 ratio. However, the relationship between the PaO2/FiO2 ratio as the dependent variable is not yet known. AIMS: To analyze the relationship between PaO2/FiO2 ratio and inflammatory biomarkers in COVID-19 patients METHOD: An analytic observational study with a retrospective, cross-sectional approach. The research sample consisted of PCR-confirmed severe and critical COVID-19 patients who were treated in the isolation room of the Ulin Hospital in Banjarmasin from August–December 2021, who met the inclusion and exclusion criteria. Data analysis used the Spearman test to see the relationship between the PaO2/FiO2 ratio and various inflammatory markers. RESULT: 52 severe and critical patients were observed according to the research flow. The number of male and female subjects (32/20) was found. The mean age was 55.38 years. The correlation test found that: there was no significant relationship between the PaO2/FiO2 ratio and IL-6 (p = 0.964), but there was a negative correlation between the PaO2/FiO2 ratio and: a).CRP (p = 0.038), b).LDH ( p<0.001), c).NLPR (p = 0.013), and d). D-dimer (p<0.001). The inflammatory biomarkers NLPR, LDH, and D-dimer are important independent variables for the severity of COVID-19, namely the PaO2/FiO2 ratio. CONCLUSION: There are a significant correlation between the PaO2/FiO2 ratio to measure the severity of Covid-19 and several inflammatory biomarkers CRP, LDH, NLPR and D-dimer